Experimental investigation of the wake behind a cooled cylinder - Pulec Jaroslav; Dančová Petra; Vinš Václav (EPJ Web of Conferences, 2022)
An experimental channel intended for investigation of a wake behind a cooled cylinder was designed and constructed in this work. The setup is designed for measurements with air at low Reynolds numbers. The measuring techniques based on the standard visualization with a fog generator and the constant temperature anemometry (CTA) were used. The flow performance was investigated behind two cylinders placed inside a channel with square cross section. One cylinder was kept at a constant flow temperature, while the second cylinder could be cooled using a water circuit with a thermostatic bath. The dependency of the Strouhal number on the Reynolds number was evaluated and compared to the literature data and the empirical correlations. The concept of an effective temperature in a non-isothermal flow was also applied. Unfortunately, a considerable difference between the preliminary measurements and the literature data was detected. The air-flow was found to have unsatisfactory high turbulence intensity. Consequently, some modifications of the current channel design are proposed.